Development of Syllable-Based Spin Wheel Media to Improve the Beginning Reading Ability of Students in Grade 1 SD / MI - Saragih, Salsabila; Devianty , Rina (FKIP - Universitas Riau, 2025)
The background of this research is related to the differences in the initial reading skills of grade 1 elementary school students, where there are some students who do not recognize vowels and consonants, and have not been able to combine or arrange syllables into the right words. The purpose of this research is to create an efficient learning tool that is proven to improve the basic reading skills of grade 1 students. The tool developed is a Rotating Wheel that focuses on Syllables. This research uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. During the development process of this tool, it has been assessed by experts in the field of media and material. The results of the assessment show that this tool is suitable for use in teaching and learning activities in class 1. The validation level for the media reaches 100% and for the material reaches 75%, both of which show numbers that are very suitable for the learning process. It can be concluded that this Rotary Wheel is very efficient in improving students' reading skills.